1999
DOI: 10.1094/cchem.1999.76.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corn Sample, Mill Type, and Particle Size on Corn Curl and Pet Food Extrudates

Abstract: Cereal Chem. 76(5):621-624The effects of corn sample, grinder type, and particle size of ground corn on the extrusion of corn curls and pet food were studied. Extrusion runs were conducted using a twin-screw extruder. Properties of corn curl and pet food extrudates were affected significantly by corn samples obtained from different parts of the country (Nebraska, Illinois, and Texas), even though grinding and extrusion parameters were held constant. The 1 Contribution No. 98-335-J from the Kansas Agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…Higher PSI values denote higher proportions of fine particles. According to Mathew, Hoseney, and Faubion (1999), fineground corn produced extrudates with higher expansion values than medium and coarse-ground corn, and also depends of the extrusion variables.…”
Section: Particle Size Distribution and Particle Size Index Of Milledmentioning
confidence: 99%
“…Higher PSI values denote higher proportions of fine particles. According to Mathew, Hoseney, and Faubion (1999), fineground corn produced extrudates with higher expansion values than medium and coarse-ground corn, and also depends of the extrusion variables.…”
Section: Particle Size Distribution and Particle Size Index Of Milledmentioning
confidence: 99%
“…Hardness (as N) was determined by measuring the maximum force required to break the extruded samples using three point break test (Singh et al, 1994;Mathew et al, 1999) with a sharp-bladed probe (55 mm wide, 40 mm high, 9 mm thick). BS (as N/mm 2 ) was determined by dividing the maximum force by cross-sectional area of the product.…”
Section: Texturementioning
confidence: 99%
“…Mathew et al (1999) working with Corn meal for pet food found that particle size and type of mill affect expansion properties and texture of pet food. Similar findings were also described by Carvalho and Ascheri (1999).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of particle size distribution of cereal grits on the final properties of extrudates has been studied to an extent already (Altan et al, 2009;Carvalho and Ascheri, 1999;Mathew et al, 1999;Desrumaux et al, 1998;Garber et al, 1997;Ryu and Lee, 1988). According to Konstance and Onwulata (2006) narrowing the particle size distribution improves the expansion of expanded extrudates.…”
Section: Introductionmentioning
confidence: 99%